Akt Regulated Phosphorylation of GSK-3β/Cyclin D1, p21 and p27 Contributes to Cell Proliferation Through Cell Cycle Progression From G1 to S/G2M Phase in Low-Dose Arsenite Exposed HaCat Cells - Chen, Yao; Liu, Xudan; Wang, Huanhuan; Liu, Shiyi; Hu, Nannan; Li, Xin (Frontiers in Pharmacology, 2019)
Arsenic is a toxic environmental contaminant. Long term exposure to arsenic through drinking water induces human cancers. However, it is as yet uncertain about the mechanisms of arsenic induced carcinogenesis. Although the effects of low-dose arsenicals on proliferation and cell cycle have been revealed by short time exposure, the evidences for long term exposure was seldom reported. The detailed mechanism has been unclear and supplemented constantly. In the present study, we used human keratinocytes (HaCat cells) to study the effects of long term, low-dose arsenite exposure on cell proliferation with emphasis on the Akt regulated cell cycle signaling pathways. We found that low-dose arsenite exposure could induce a dose dependent increase of cell proliferation and promotion of cell cycle progression from G1 to S/G2M phase, which could be attenuated by MK2206, a high selective inhibitor of Akt. Along with the dose dependent increase of phospho-AKT expression, the dose dependent increases of phospho-GSK-3β (Ser 9), phospho-p21 (Thr 145), phospho-p27 (Thr 157) and total cyclin D1 expression, and the dose dependent decreases of phospho-cyclin D1 (Thr 286) , p21 and p27 expression were also found in the arsenite exposed cells. Treatment with MK2206 could markedly reverse the expression of all of the above proteins. Our findings indicated that the phosphorylated activation of Akt played a role in the proliferation of HaCat cells upon long term, low-dose arsenite exposure through the phosphorylative regulation of its downstream cell cycle regulating factors of GSK-3β/cyclin D1, p21 and p27 which could induce the promotion of cell cycle progression from G1 to S/G2M phase.